Application of the Precautionary Principle in Judge's Legal Considerations for Pollution Cases in Islamic Law Perspectives - Triana, Nita; Khashogi, Luqman Rico; Turistiati, Ade Tuti; Monk, Lincoln James Faikar (al-'adalah, 2023)
In industrial activities, the precautionary principle in protecting the environment is very important. This research examines how judges use the precautionary principle in making legal decisions in cases of environmental pollution. This research is a doctrinal qualitative with a normative juridical approach. Based on the research findings, the Panel of Judges in the decision of the North Jakarta District Court Number: 735/PDT.G-LH/2018/PN.Jkt.Utr determined that PT. HAYI has carelessly disposed of B3 waste from textile industry activities. In that decision, the Panel of Judges expanded the understanding of the Precautionary Principle, from the level of management and preventive policies to the level of repressive dispute resolution. The judge has also changed the Rio Declaration which is only morally binding to a hard law which is directly used as a source of law in deciding a case. This development is a paradigm shift in environmental justice from homocentric to ecocentric. In Islamic Law, the precautionary principle is related to the concept of ihtiyāth(prudence) and correlates with sadd al-dzarī'ah, namely the maximum effort to suppress everything that can be a means of prohibited things to avoid the amount of damage. Within the framework of Usul Fiqh, avoiding damage is a priority step rather than reaping benefits.